Tuning oxygen vacancy and growth step for the high performance of Nd1+xBa2−xCu3Oy bulk cryomagnets. Issue 32 (31st July 2020) - Huang, Simin; Zhuang, Yufeng; Zhu, Yanhan; Yin, Yiqian; Wan, Yan; Zhou, Difan; Chaud, Xavier; Zhou, Ligang; Yao, Xin
Abstract : The Nd1+ x Ba2− x Cu3 O y superconductor is considered to be one of the most promising materials in the REBaCu3 O y family owing to its excellent properties of high critical transition temperature ( T c ) and high current density. Abstract : The Nd1+ x Ba2− x Cu3 O y superconductor is considered to be one of the most promising materials in the REBaCu3 O y family owing to its excellent properties of high critical transition temperature ( T c ) and high current density. However, the substitution of Nd on the Ba site occurs easily with this cation non-stoichiometric oxide, particularly in the ambient air, during the melt growth process, leading to a severe deterioration in the superconducting performance. Here, we combined thermodynamic with kinetic methods, namely the composition-control melt-growth (CCMG) and cooling-rate-control melt-growth (CRCMG) method, for the synthesis. We used Ba-rich precursors in the air-processed CCMG, which underwent an optimal cooling step (CRCMG) for increasing the chemical potential of Ba and tuning the oxygen vacancy during the growth. As a result, the Nd1+ x Ba2− x Cu3 O y bulk could reach a high T c of 95 K in air. In the peritectic reaction, it was found that the higher cooling rate reduces the absorption of oxygen during the formation of Nd1+ x Ba2− x Cu3 O y, resulting in the reduction of the whole cation valence, and therefore, a low x value in Nd1+ x Ba2− x Cu3 O y was gained. In addition, considering their brittle nature and discontinuous growth trend, Nd1+ x Ba2− x Cu3 O y superconductor bulks were optimized for the growth step in a gradual acceleration cooling rate mode. As a result, the cryomagnet (16 mm in diameter) with a high T c of 95 K and a trapped field of 0.60 T, superior to the previously reported air-processed ones, was successfully obtained. This success in the control of the cation stoichiometry and growth mode opens a promising pathway for the preparation of more functional oxides.